Critically reflecting on the use of immersive virtual reality in educational settings: What is known and what has yet to be shown? (Journal of Applied Learning and Teaching, 2023)
Interest in the educational applications of immersive virtual reality (IVR) has continued to grow worldwide, particularly in recent years. With the ever-increasing literature base on IVR in educational contexts, two patterns of data have emerged: one focused on the affective component and one focused on the cognitive component of IVR. Research focused on the affective component of this technology has consistently found that it is beneficial in increasing students’ motivation to learn. However, there is less of a consensus in the literature on the cognitive benefits of IVR, with results sometimes indicating it (a) is an effective tool for learning, (b) is not an effective tool for learning, and (c) is similar to other instructional media in its impact on learning outcomes. As suggested by these inconsistent findings, there is a great deal left to be understood about when and how IVR can be effective for learning. Therefore, the goal of this reflection article is to draw attention to important research gaps that, if filled, may help to explain the inconsistent effects of this technology in the research literature. Additionally, this article highlights areas in need of further research, which we hope will aid in the advancement of knowledge surrounding the effective implementation of IVR in education.